Use of self-employment in violation of health and safety regulations and the Minimum Wage Act – conclusions from NCN project No. 2018/29/B/HS5/02534 (The use of atypical forms of employment in violation of labour and social security laws - diagnosis and prospects for the future, 2023)
The purpose of this article is to show the causes and circumstances of the use of self-employment in violation of health and safety regulations and the Minimum Wage Act, and to try to find solutions to effectively and efficiently combat this pathology. The legal solutions in force in this respect are not sufficient and the scale of abuse appears to be significant. De lege lata, the Polish legislator does not guarantee gainfully self-employed people an adequate level of protection in such fundamental areas for every working person as life and health and remuneration – the pillars of a safe, honest and fair working environment. The presented considerations constitute a fragment of the research conducted under the supervision of Prof. Tomasz Duraj, PhD, of the University of Łódź, within the framework of a scientific grant financed from the funds of the National Science Centre (contract no. UMO- 2018/29/B/HS5/02534 for research project no. 2018/29/B/HS5/02534).